Canadian women's experiences in mixed-sex sport: Wheelchair rugby - Corrigan, Bronwyn; Misener, Laura (Frontiers in Sports and Active Living, 2023)
Wheelchair rugby was developed in Canada in the 1970s and named an official Paralympic sport in 2000. Wheelchair rugby is one of the few Paralympic or Olympic sports that includes mixed-sex participation. Where historically women with disabilities 1 have had limited access to elite sporting competition, wheelchair rugby provides the opportunity for women to represent themselves as competitive and physical beings, capable of the physicality and aggressive nature of the sport alongside men. This project looks to fill the gap in research considering women's experiences in these potentially highly gendered sport settings. This study uses a thematic analysis approach to explore female athletes' lived experiences of participation in wheelchair rugby. Five provincial athletes were interviewed and shared their complex experiences competing in wheelchair rugby.